2011
DOI: 10.1016/j.sjopt.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular mycosis at a referral center in Saudi Arabia: A 20-year study

Abstract: In contrast to other studies on fungal keratitis, Aspergillusspp. and Trichophyton sp. were the most commonly isolated fungal pathogens; the former carries the worst prognosis. Risk factors included previous intraocular surgery and trauma. Poor outcome was associated with Aspergillus spp., delayed presentation, previous intraocular surgery and late surgical intervention. This study recommends early surgical intervention to improve the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
19
0
4
Order By: Relevance
“…Salera et al found 60% of infections by Fusarium and 30% by Aspergillus, both filamentous fungi (17) ; Santos et al also found a predominance of filamentous fungi, but the most common were Penicillium and Cladosporium (16) ; Carvalho et al found that filamentous fungi were relatively more common, with 32% by Fusarium, 17% by Aspergillus and 10% by Penicillium (18) ; Dalfré et al found 44% by Fusarium and 23% by Geotricum (14) . With regard to other countries, in the United States Aspergillus was the most frequently isolated fungus; in Saudi Arabia, the most common were Aspergillus and Trycophytum, both filamentous (22) ; in Japan, Fusarium and Aspergillus (23) ; in India, Fusarium and Aspergillus were also the most frequent (24) ; and the same was found in China, where filamentous fungi were found in 90% of cases (25) . Table 3 shows the high number of cases related to previous surgery.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Salera et al found 60% of infections by Fusarium and 30% by Aspergillus, both filamentous fungi (17) ; Santos et al also found a predominance of filamentous fungi, but the most common were Penicillium and Cladosporium (16) ; Carvalho et al found that filamentous fungi were relatively more common, with 32% by Fusarium, 17% by Aspergillus and 10% by Penicillium (18) ; Dalfré et al found 44% by Fusarium and 23% by Geotricum (14) . With regard to other countries, in the United States Aspergillus was the most frequently isolated fungus; in Saudi Arabia, the most common were Aspergillus and Trycophytum, both filamentous (22) ; in Japan, Fusarium and Aspergillus (23) ; in India, Fusarium and Aspergillus were also the most frequent (24) ; and the same was found in China, where filamentous fungi were found in 90% of cases (25) . Table 3 shows the high number of cases related to previous surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Similar results were found in Saudi Arabia. Jastaneiah et al found that 38.7% of cases had surgery prior to the diagnosis of fungal keratitis (22) . As can be seen in Figures 1C and 1D, the organisms remain on the surface of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in its incidence has been reported in recent decades (4)(5)(6) , but the disease is still a challenge in terms of diagnosis and treatment (5,7) . Regarding microbial ceratites, fungal ceratites are reported in 16.4% of cases in Parana (Brazil) (8) , 10.3% and 14.0% of cases in Saudi Arabia (5,9) , 8% of cases in San Francisco (California, United States) (10) and 38.06%, 39.8% and 36.79% of cases in India (2,11,12) . Two basic forms of fungal keratitis are recognized: one due to filamentous fungi (especially Fusarium and Aspergillus) which commonly occurs in tropical and subtropical zones, and another due to yeast fungi or related (in particular Candida) (13) .…”
mentioning
confidence: 99%
“…However, most epidemiological studies on mycotic keratitis are based on observations of corneal material used to prepare the slides and/or culture (4,8,9,11,12,18) . Few studies talk about histopathological characteristics of fungal keratitis (22) or mention a histopathological examination carried out during the study of the epidemiology of fungal keratitis (2,5,16,20) . Among the latter, none uses exclusive information for the histopathological exam, Bras Oftalmol.…”
mentioning
confidence: 99%
See 1 more Smart Citation